Contemporary Evaluation and Management of the Diabetic Foot - Bauer E. Sumpio (Scientifica)
Foot problems in patients with diabetes remain a major public health issue and are the commonest reason for hospitalization of patients with diabetes with prevalence as high as 25%. Ulcers are breaks in the dermal barrier with subsequent erosion of underlying subcutaneous tissue that may extend to muscle and bone, and superimposed infection is a frequent and costly complication. The pathophysiology of diabetic foot disease is multifactorial and includes neuropathy, infection, ischemia, and abnormal foot structure and biomechanics. Early recognition of the etiology of these foot lesions is essential for good functional outcome. Managing the diabetic foot is a complex clinical problem requiring a multidisciplinary collaboration of health care workers to achieve limb salvage. Adequate off-loading, frequent debridement, moist wound care, treatment of infection, and revascularization of ischemic limbs are the mainstays of therapy. Even when properly managed, some of the foot ulcers do not heal and are arrested in a state of chronic inflammation. These wounds can frequently benefit from various adjuvants, such as aggressive debridement, growth factors, bioactive skin equivalents, and negative pressure wound therapy. While these, increasingly expensive, therapies have shown promising results in clinical trials, the results have yet to be translated into widespread clinical practice leaving a huge scope for further research in this field.